The intersection of dakwah message and social expression in the lyrics of the song "Judi" by Rhoma Irama - Hidayat, Yogi Fery (Jurnal Penelitian Humaniora, 2024)
The song "Judi" by Rhoma Irama critiques gambling through its preaching and social criticism. Released during the New Order era, it highlights the negative impacts of widespread gambling on individuals and communities. This study examines the intersection of preaching messages and social expressions in the song's lyrics using a sociolinguistic approach. The research employs qualitative methods, analyzing social, cultural, and linguistic aspects. Findings indicate that the song critiques the moral and financial harm caused by gambling. Culturally, it emphasizes values such as hard work and integrity. Linguistically, Rhoma Irama uses simple yet persuasive language, making the preaching message accessible to all audiences. The song delivers a strong religious message, prohibiting gambling while highlighting its detrimental effects on life and faith. In conclusion, "Judi" serves not only as social criticism but also as a preaching medium, remaining relevant today by promoting moral and religious values in society.